A μSR study of the spin-crossover - Blundell, S; Pratt, F; Steer, C; Marshall, I; Létard, J (2004)
The spin-crossover phenomenon is a cooperative low-spin to high-spin transition which can be initiated using temperature or light-irradiation. We have used muon-spin relaxation (μSR) to study this effect in Fe(PM-PEA) 2(NCS)2 and Fe(PMAzA)2(NCS)2. We find Gaussian or exponential muon relaxation in the high-spin phase for the two compounds, reflecting differences in their intermolecular interactions. For both compounds, the low-spin phase gives rise to root-exponential relaxation which we associate with a dilute distribution of fluctuating moments resulting from incomplete spin crossover. © 2003 Elsevier Ltd. All rights reserved.